Análise Semiótica de Sinais Fotométricos: II - Construção de Redundâncias de Ordem Superior - Vieira, Jorge de Albuquerque (Anuário do Instituto de Geociências, 1985)
We present the computation of the redundancies of higher levels in a natural language outlined in photometrical signals. The semantical content refers to aspects of the local pollution of the Rio de Janeiro sky. A basic codification, the alphabet and the first order redundance were developed in previous papers. Problems concerning the growth of alphabet and a quantitative analysis of tipical "words" in the phenomenous are also studied.